PENGEMBANGAN OBJEK AGROWISATA PAYO KECAMATAN LUBUK SIKARAH KOTA SOLOK - ZULFAHMI ZULFAHMI; Sri Mariya (JURUSAN GEOGRAFI FIS UNP, 2019)
Abstract The research aims to find out about: 1) Internal factors (strengths and weaknesses), 2) External factors (opportunities and threats) and 3) Strategies suitable for the development of Payo Agro Tourism Objects. This type of research is descriptive qualitative using SWOT analysis. Data collection techniques used were observation, interviews and documentation. The research subjects used were 1 tourism agency, around 5 people, 15 visitors. Data analysis techniques used include data reduction, data presentation and drawing conclusions. The results of the study are: 1) The power of Payo Agro Tourism Objects is an attractive tourist attraction. The road is smooth and good with a fairly wide physical road condition. Weaknesses of these attractions are: difficult to reach because of the high places to make steep and climbing roads, seen from the environment whose name is still developing and the lack of facilities or facilities available in Payo Agro Tourism Objects. 2) Threats to Payo Agro Tourism Objects are the lack of interest of tourists to visit and the availability of Strategic Rice Fields in Solok. While the opportunities that can be developed in Payo Agro Tourism Objects can be developed as recreational tourism. 3) The strategy taken is to increase the vehicle, add transportation for visitors, add facilities that do not yet exist in Payo Agro Tourism Objects as recreational tourism, such as: toilets/toilets, seating/gazebos, parking lots, canteen/stalls as recreational tourism, inviting or involving visitors and the surrounding community to protect the environment of Payo Agro Tourism Objects. make good use of access, improve food stalls by the community to sell distinctive plants, provide counseling on the importance of tourism awareness, improve cooperation with the government.